A dual removable activating group enabled the Povarov reaction of N-arylalanine esters: synthesis of quinoline-4-carboxylate esters. Issue 14 (14th March 2017) - Jia, Xiaodong; Lü, Shiwei; Yuan, Yu; Zhang, Xuewen; Zhang, Liang; Luo, Liangliang
Abstract : A dual removable activating group enabled Povarov reaction of N -arylalanine esters was reported. Abstract : A dual removable activating group enabled Povarov reaction of N -arylalanine esters was reported. N -Arylalanine ester was utilized as the sole carbon source to generate N -arylimine and its tautomer, enamine, in situ by aerobic oxidation of sp 3 C–H bonds, and then the consecutive reaction delivered the desired quinoline-4-carboxylate esters in high yields.